GPlates: Building a Virtual Earth Through Deep Time. (12th July 2018) - Müller, R. Dietmar; Cannon, John; Qin, Xiaodong; Watson, Robin J.; Gurnis, Michael; Williams, Simon; Pfaffelmoser, Tobias; Seton, Maria; Russell, Samuel H. J.; Zahirovic, Sabin
Abstract: GPlates is an open‐source, cross‐platform plate tectonic geographic information system, enabling the interactive manipulation of plate‐tectonic reconstructions and the visualization of geodata through geological time. GPlates allows the building of topological plate models representing the mosaic of evolving plate boundary networks through time, useful for computing plate velocity fields as surface boundary conditions for mantle convection models and for investigating physical and chemical exchanges of material between the surface and the deep Earth along tectonic plate boundaries. The ability of GPlates to visualize subsurface 3‐D scalar fields together with traditional geological surface data enables researchers to analyze their relationships through geological time in a common plate tectonic reference frame. To achieve this, a hierarchical cube map framework is used for rendering reconstructed surface raster data to support the rendering of subsurface 3‐D scalar fields using graphics‐hardware‐accelerated ray‐tracing techniques. GPlates enables the construction of plate deformation zones—regions combining extension, compression, and shearing that accommodate the relative motion between rigid blocks. Users can explore how strain rates, stretching/shortening factors, and crustal thickness evolve through space and time and interactively update the kinematics associated with deformation. Where data sets described by geometries (points, lines, or polygons) fall within deformation regions, the deformation can be applied to these geometries. Together, these tools allow users to build virtual Earth models that quantitatively describe continental assembly, fragmentation and dispersal and are interoperable with many other mapping and modeling tools, enabling applications in tectonics, geodynamics, basin evolution, orogenesis, deep Earth resource exploration, paleobiology, paleoceanography, and paleoclimate. Plain Language Summary: The GPlates virtual globe software provides the capability to reconstruct geodata attached to tectonic plates to develop and modify models that describe how the plates and their boundaries have evolved through time. It allows users to deform plates and to visualize surface tectonics in the context of convecting mantle structure and evolution by importing seismic tomography models or outputs from geodynamic models. GPlates applications include tectonics, geodynamics, basin evolution, orogenesis, deep Earth resource exploration, paleobiology, paleoceanography, and paleoclimate. The software is enabling end‐users in universities, government organizations, industry, and schools to explore the evolution of planet Earth on their desktop. Key Points: GPlates is an open‐source plate tectonic geographic information system, enabling the interactive manipulation of tectonic reconstructions GPlates enables the building of topological plate models, including plate deformation, and allows the visualization of subsurface volumes GPlates applications include tectonics, geodynamics, basin evolution, orogenesis, resource exploration, paleobiology, and paleoclimate